A generalization of operator stochastic integrals - Gorbunov, A. V.; Горбунов, А. В.; Горбунов, А. В. (Institute of Mathematics, NAS of Ukraine, 1994)
We generalize the method for construction of operator stochastic integrals suggested by Berezanskii, Zhernakov, and Us. We extend the class of integrable commutative quantum processes and study properties of corresponding integrals.